\(1/4*5/12+5/12*4/5 \) tính bằng hai cách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (15 +35) : 5 = ?
Cách 1: (15 +35) : 5
= 50 : 5 = 10
Cách 2: (15 +35) : 5
= 15 : 5 + 35 : 5
= 3 + 7 = 10
+) (80 +4) : 4 = ?
Cách 1:(80 +4) : 4
= 84 : 4 = 21
Cách 2:(80 +4) : 4
= 80 : 4 + 4 :4 = 20 +1 = 21
b) 18 : 6 + 24 : 6 = ?
Cách 1: 18 : 6 + 24 : 6
= 3 + 4 = 7
Cách 2: (18 + 24) : 6
= 42 : 6 = 7
+) 60 : 3 + 9 : 3 =?
Cách 1: 60 : 3 + 9 : 3
= 20 + 3 = 23
Cách 2: 60 : 3 + 9 : 3
=(60 +9) : 3 = 23
a) (15 +35) : 5 = ?
Cách 1: (15 +35) : 5
= 50 : 5 = 10
Cách 2: (15 +35) : 5
= 15 : 5 + 35 : 5
= 3 + 7 = 10
+) (80 +4) : 4 = ?
Cách 1:(80 +4) : 4
= 84 : 4 = 21
Cách 2:(80 +4) : 4
= 80 : 4 + 4 :4 = 20 +1 = 21
b) 18 : 6 + 24 : 6 = ?
Cách 1: 18 : 6 + 24 : 6
= 3 + 4 = 7
Cách 2: (18 + 24) : 6
= 42 : 6 = 7
+) 60 : 3 + 9 : 3 =?
Cách 1: 60 : 3 + 9 : 3
= 20 + 3 = 23
Cách 2: 60 : 3 + 9 : 3
=(60 +9) : 3 = 23
HTa) 8 × 5 × 9 = (8 × 5) × 9 = 40 × 9 = 360
b) 6 × 7 × 5 = (6 × 5) × 7= 30 × 7= 210
c) 6 × 4 × 25 = 6 × (4 × 25) = 6 × 100= 600
Bài 1:
a) Ta có: \(\dfrac{2}{5}\cdot x+\dfrac{1}{3}=\dfrac{1}{5}\)
\(\Leftrightarrow\dfrac{2}{5}\cdot x=\dfrac{1}{5}-\dfrac{1}{3}=\dfrac{-2}{15}\)
\(\Leftrightarrow x=\dfrac{-2}{15}:\dfrac{2}{5}=\dfrac{-2}{15}\cdot\dfrac{5}{2}\)
hay \(x=-\dfrac{1}{3}\)
Vậy: \(x=-\dfrac{1}{3}\)
b) Ta có: \(\dfrac{1}{5}+\dfrac{5}{3}:x=\dfrac{1}{2}\)
\(\Leftrightarrow\dfrac{5}{3}:x=\dfrac{1}{2}-\dfrac{1}{5}=\dfrac{3}{10}\)
\(\Leftrightarrow x=\dfrac{5}{3}:\dfrac{3}{10}=\dfrac{5}{3}\cdot\dfrac{10}{3}\)
hay \(x=\dfrac{50}{9}\)
Vậy: \(x=\dfrac{50}{9}\)
c) Ta có: \(\dfrac{4}{9}-\dfrac{5}{3}\cdot x=-2\)
\(\Leftrightarrow\dfrac{5}{3}x=\dfrac{4}{9}+2=\dfrac{22}{9}\)
\(\Leftrightarrow x=\dfrac{22}{9}:\dfrac{5}{3}=\dfrac{22}{9}\cdot\dfrac{3}{5}\)
hay \(x=\dfrac{22}{15}\)
Vậy: \(x=\dfrac{22}{15}\)
d) Ta có: \(\dfrac{5}{7}:x-3=\dfrac{-2}{7}\)
\(\Leftrightarrow\dfrac{5}{7}:x=\dfrac{-2}{7}+3=\dfrac{19}{21}\)
\(\Leftrightarrow x=\dfrac{5}{7}:\dfrac{19}{21}=\dfrac{5}{7}\cdot\dfrac{21}{19}\)
hay \(x=\dfrac{15}{19}\)
Vậy:\(x=\dfrac{15}{19}\)
\(\dfrac{1}{4}\times\dfrac{5}{12}+\dfrac{5}{12}\times\dfrac{4}{5}=\dfrac{5}{12}\times\left(\dfrac{1}{4}+\dfrac{4}{5}\right)=\dfrac{5}{12}\times\left(\dfrac{5}{20}+\dfrac{8}{20}\right)=\dfrac{5}{12}\times\dfrac{13}{20}=\dfrac{13}{48}\)
\(C_1:\dfrac{1}{4}\times\dfrac{5}{12}+\dfrac{5}{12}\times\dfrac{4}{5}=\dfrac{5}{48}+\dfrac{1}{3}=\dfrac{7}{16}\)
\(C_2:\dfrac{1}{4}\times\dfrac{5}{12}+\dfrac{5}{12}\times\dfrac{4}{5}=\dfrac{5}{12}\times\left(\dfrac{1}{4}+\dfrac{4}{5}\right)=\dfrac{5}{12}\times\dfrac{21}{20}=\dfrac{7}{16}\)